Performance of cell-free DNA sequencing-based non-invasive prenatal testing: experience on 36,456 singleton and multiple pregnancies - Marco La Verde; Luigia De Falco; Annalaura Torella; Giovanni Savarese; Pasquale Savarese; Raffaella Ruggiero; Anna Conte; Vera Fico; Marco Torella; Antonio Fico (BMC, 2021)
Abstract Background This paper describes the clinical practice and performance of cell-free DNA sequencing-based non-invasive prenatal testing (NIPT) as a screening method for fetal trisomy 21, 18, and 13 (T21, T18, and T13) and sex chromosome aneuploidies (SCA) in a general Italian pregnancy population. Methods The AMES-accredited laboratory offers NIPT in maternal blood as a screening test for fetal T21, T18, T13 and SCA. Samples were sequenced on a NextSeq 550 (Illumina) using the VeriSeq NIPT Solution v1 assay. Results A retrospective analysis was performed on 36,456 consecutive maternal blood samples, including 35,650 singleton pregnancies, 800 twin pregnancies, and 6 triplet pregnancies. Samples were tested between April 2017 and September 2019. The cohort included 46% elevated-risk and 54% low-risk patients. A result indicative of a classic trisomy was found in 356 (1%) of singleton or twin samples: 254 T21, 69 T18, and 33 T13. In addition, 145 results (0.4%) were indicative of a SCA. Of the combined 501 screen-positive cases, 484 had confirmatory diagnostic testing. NIPT results were confirmed in 99.2% (247/249) of T21 cases, 91.2% (62/68) of T18 cases, 84.4% (27/32) of T13 cases, and 86.7% (117/135) of SCA cases. In the 35,955 cases reported as unaffected by a classic trisomy or SCA, no false negative cases were reported. Assuming that false negative results would be reported, the sensitivity of NIPT was 100.00% for T21 (95% Cl 98.47-100.0), T18 (95% Cl 94.17-100.0), and T13 (95% Cl 87.54-100.0). The specificities were 99.99% (95% Cl 99.98-100.0), 99.98% (95% Cl 99.96-100.0), 99.99% (95% Cl 99.97-100.0), and 99.95% (95% Cl 99.92-99.97) for T21, T18, T13, and SCA, respectively. Conclusion This retrospective analysis of a large cohort of consecutive patients who had whole-genome sequencing-based NIPT for classic trisomies and SCA shows excellent detection rates and low false positive rates.